Aortic pulse wave velocity predicts cardiovascular mortality in middle-aged and elderly Japanese men - Inoue, Noriko; Maeda, Ryo; Kawakami, Hideshi; Shokawa, Tomoki; Yamamoto, Hideya; Ito, Chikako; Sasaki, Hideo (Circulation journal : official journal of the Japanese Circulation Society, 2009)
Aortic pulse wave velocity (PWV) is widely used as a noninvasive index of arterial stiffness and was used in the present study to investigate the relationship between PWV and cardiovascular mortality in the middle-aged and elderly Japanese population using a longitudinal study design. From 1988 to 2003, a total of 3,960 men (50-69 years old at baseline) who underwent medical check-ups and measurement of PWV, which was standardized for diastolic blood pressure, were recruited and divided into 4 groups according to the PWV values. The average follow-up period was 8.2 years. Mortality from all-causes and from cardiovascular disease significantly increased as PWV increased in the entire follow-up period. Multivariate-adjusted relative risks of all-cause and cardiovascular disease mortality for the highest quartile of PWV (>9.0 m/s) were 1.28 (95% confidence interval (CI) 0.97-1.68) and 1.83 (95%CI 1.02-3.29), respectively, compared with the lowest quartile (<7.5 m/s). An increased PWV can predict cardiovascular mortality in middle-aged and elderly Japanese men.